Determinant of Islamic Banking Profitability In Indonesia - Dimas Puja Kuswara; Etty Puji Lestari; Tri Kurniawati Retnaningsih (LPPM Universitas Terbuka, 2019)
Finding a determinant of profitability has become one of the most popular topics in banking research. Previous research has identified many factors that significantly influence bank profitability. There are also many studies that measure the effectiveness of sharia banking globally, but few analyze the profitability issues of sharia banks. This study aims to analyze the impact of factors affecting profitability in Islamic Banks listed on the Indonesia Stock Exchange. The method used is multiple linear regression analysis. The variables are return on assets as dependent variable and murabahah, musyarakah, mudharabah, branch office, cash office, and Automatic Teller Machine as independent variable. This study found that funding factors such as murabaha, musharaka and conventional and electronic networking factors such as Branch Office, Cash Office, and ATM had positive and significant impact on profitablity of Sharia Bank, while mudharabah had a negative and significant influence on profitablitas Sharia Bank. Sub-Branch Offices also had a negative but insignificant effect on the profitability of Sharia Banks. This result indicated that income on management became the most dominant income in generating profit of sharia banking. However, the management of funds could not work if not supported by Islamic banking channeling tools.